2017
DOI: 10.1021/acs.analchem.7b01362
|View full text |Cite
|
Sign up to set email alerts
|

Single Palladium Nanoparticle Collisions Detection through Chronopotentiometric Method: Introducing a New Approach to Improve the Analytical Signals

Abstract: In the present research, the chronopotentiometric method and hydrazine, as a suitable probe, were used to detect single Pd nanoparticle (Pd-NP) collisions to the surface of a carbon fiber ultramicroelectrode (CFUME). The change in the potential, which is due to the electrocatalytic oxidation of hydrazine exactly at the time of Pd-NP collision to the CFUME surface, was used to detect each collide. It was shown that the amplitude and the frequency of the potential steps, produced through the nanoparticles collis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…In previous studies, collision experiments with the Pd NP using the hydrazine oxidation reaction showed a “blip” response [ 26 ]. However, when the hydrogen peroxide reduction was used with a Pt NP, a “staircase” response was obtained similar to our result [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, collision experiments with the Pd NP using the hydrazine oxidation reaction showed a “blip” response [ 26 ]. However, when the hydrogen peroxide reduction was used with a Pt NP, a “staircase” response was obtained similar to our result [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies at the single NP level have been reported for Pd NPs. Recently, Zare group reported firstly the collision of a single NP of Pd for the hydrazine oxidation reaction using a chronopotentiometric method [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Detection of stochastic collisions of nano-objects on an electrode has been a research topic of interest in recent years. [1][2][3] Since the first observation of hard nanoparticle collisions by implementation of ultramicroelectrodes (UMEs), 4 detection and statistical analysis of the electrode collisions of many types of nanoobjects were studied, including those of hard nanoparticles, [5][6][7][8] soft nanoparticles, [9][10][11] and biologically relevant entities. [12][13][14][15] More recent adaptations of the electrochemical collision research empowered scientists to utilize these stochastic collisions as a synthetic tool.…”
mentioning
confidence: 99%
“…Since the first reported observation of the single particle collision events through electrocatalytic amplification, this approach has been extensively applied to examine the correlation between particle structure and catalytic function . Significant progress has been made so far to elucidate the impact of collision-induced catalytic reactions and to understand the complex mass transfer of nanocatalysts as well. , The collision behaviors of a wide range of metal or metal oxide nanoparticles have been studied including platinum, gold, palladium, iridium oxide, or ruthenium oxide; the influence of several different ultramicroelectrodes (UME) such as carbon, gold, platinum, and mercury/platinum has also been explored. Nevertheless, there is no previous work on single carbon nanotube (CNT) collision, to the best of our knowledge, except one early attempt to attach gold nanoparticle tethered CNT on a platinum electrode …”
mentioning
confidence: 99%